Media Work as Field Advancement: The Case of Science Media Center Germany - Buschow, Christopher (2022)
In the wake of the news industry’s digitization, novel organizations that differ considerably from traditional media firms in terms of their functional roles and organizational practices of media work are emerging. One new type is the field repair organization, which is characterized by supporting high-quality media work to compensate for the deficits (such as those which come from cost savings and layoffs) which have become apparent in legacy media today. From a practice-theoretical research perspective and based on semi-structured interviews, virtual field observations, and document analysis, we have conducted a single case study on Science Media Center Germany (SMC), a unique non-profit news start-up launched in 2016 in Cologne, Germany. Our findings show that, in addition to field repair activities, SMC aims to facilitate progress and innovation in the field, which we refer to as field advancement. This helps to uncover emerging needs and anticipates problems before they intensify or even occur, proactively providing products and tools for future journalism. This article contributes to our understanding of novel media organizations with distinct functions in the news industry, allowing for advancements in theory on media work and the organization of journalism in times of digital upheaval.